The relation between quality of clinical trials and acupuncture efficacy - Nordon, David Gonçalves (Revista da Faculdade de Ciências Médicas de Sorocaba, 2013)
Introduction: Clinical trials of acupuncture not always have concordant results, mostly due to their great heterogeneity. Two indexes have been developed to analyze the quality of acupuncture trials. This study hypothesizes that, the more adequate the intervention and the control techniques, the more efficacious the acupuncture. Methods: Both indexes were applied to 27 randomized clinical trials comparing acupuncture to placebo. Results were compared by using the Mann-Whitney test. Results: Studies favorable to acupuncture had a intervention score’s median of 11.5; for the unfavorable ones, it was 7, p: 0.0017. Articles with and without statistically significant differences, though, had the same median for their scores in the control index: 6. Discussion: There is a positive relation between a better score for acupuncture technique and a statistically significant difference between acupuncture and interventional control. However, due to the little heterogeneity in the degree of physiological effect from each article, the control index had no statistical significance. Conclusion: This study established that, among acupuncture RCT controlled by placebo or sham of moderate physiological effect, the adequacy of the technique is more important than the adequacy of control in establishing a statistically significant difference between acupuncture and interventional control.